Strategi Guru Pendidikan Agama Islam dalam Mengatasi Phubbing (Phone Snubbing) Siswa MA Raden Fatah Grobog Wetan Tegal - Abdullah Azzam; Moh. Sobirin; Pindha Kaptiningrum; Indah Solekha; Hilwa Nabila; Nur Rafika (CV Kalimasada Group, 2024)
One modern phenomenon known as “phone snubbing”, where a person focuses on their phone rather than interacting with others, negatively impacts communication and social relationships. The type of research used is field research with a qualitative descriptive method, which is employed to describe, reveal, and explain phenomena or issues in the educational environment. Data was collected through observations and in-depth interviews with Islamic Education teachers. Research shows that religious education teachers use religious educational materials to instill moral and ethical values. They also implement extracurricular activities that support social interaction and develop students character. The collaboration between Islamic Education teachers and guidance counselors is very important for monitoring responsible technology use. To reduce phubbing, this research suggests enhancing digital education, parental involvement, and regular assessments.